Women in blue: Meaning and identity perspectives of policewomen within the South African Police Services in the Cape Town Metropolitan area. - Zondeka, Kuhle Nwabisa (Department of Public Law, 2025)
South Africa grapples with a policing crisis marked by rising gender-based violence, corruption, high violent crime rates, robbery, and murder. Effective solutions to improve policing require holistic police reform, addressing internal issues including gender inequality. This study examines the experiences of policewomen in the South African Police Service (SAPS), uncovering their challenges with their male counterparts in the workplace as well as the communities they serve in. Through open-ended interviews, the research reveals discrimination based on capabilities, workplace sexual harassment, and societal devaluation of policewomen as challenges policewomen experience. By applying an intersectional feminist lens, the study recognises the intricate identities of policewomen that are shaped by the intersection of gender and race in a male-dominated society. Policewomen in the SAPS face consistent and constant challenges, however, they continue to demonstrate resilience against mistreatment from colleagues, the public, and superiors. The study concluded that the experience of being a woman in the SAPS defies a simple narrative and lacks a clear formula. This unique experience demands constant efforts to overcome adversities and contribute to changing dynamics within policing. Furthermore, the study showed that policewomen play a crucial role in police reform, standing resilient amid challenges, exemplifying strength, and paving the way for a more inclusive and equitable policing environment.